Developing a finite element model for thermal analysis of friction stir welding by calculating temperature dependent friction coefficient - Meyghani, B. (Springer Heidelberg, 2017)
One of the main sources of the heat generation during the Friction Stir Welding (FSW) process is the friction force. There is a need to define the friction coefficient in order to accurately predict the simulated model. Many authors assumed the friction coefficient as a constant value. However, such assumptions may affect the reliability of the results obtained. In this paper, ABAQUS® software is used to simulate thermal behavior during the FSW process. In order to calculate temperature dependent friction coefficient values, the Coulomb friction law is modified in MATLAB®. The results show that the heat generation strongly depends on the motion of the welding tool which is a combination of rotational and transverse speeds. Furthermore, the rise of the rotational speed increases the welding temperature, because of the higher friction heating, higher stirring, and higher mixing of the material. In contrast, the increase of the transverse speed decrease the welding temperature. The results also demonstrate that the temperature profile during the welding is asymmetrically distributed in the welding cross section (temperature being higher on the advancing side). Experimental measurements have been conducted to validate the temperature profile. In conclusion, the simulation results are consistent with the experimental data as well as published results. © Springer Nature Singapore Pte Ltd. 2017.